Formulation and in vitro Assessment of Eudragit L 100 and Eudragit S 100 Based Naproxen Microspheres (Dhaka University Journal of Pharmaceutical Sciences, 2016)
In the present study naproxen loaded microspheres were prepared by emulsification solvent evaporation method in order to achieve targeted drug delivery. Eudragit L 100 and Eudragit S 100 were used as the rate retardant polymers in the preparations. Thirteen formulations (F1-F13) were prepared using 22 factorial design by changing the concentration of these two polymers. All the formulations were evaluated for product yield, drug content, entrapment efficiency, particle size and drug release profiles. Highest drug content and entrapment efficiency were found to be 30.17% (F4) and 91.86% (F8) respectively. The particle size was found to be 159.26-234.70 ?m for all formulations. In-vitro drug release studies were performed using USP type II (Paddle) apparatus for 8 hrs in pH 7.4 phosphate buffer. The maximum drug release after 8 hrs was found to be 60.19% for batch F4. The release kinetics of all formulations were evaluated by using zero order, first order, Higuchi, Korsmeyer-Peppas, Kopcha and Hixson Crowell model. Almost all formulations fitted best with the Kopcha kinetic model. The SEM study indicated the spherical structure of the microspheres having rough surfaces.Dhaka Univ. J. Pharm. Sci. 15(1): 47-55, 2016 (June)